Científicos en 90 minutos. - Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940- (Siglo XXI de España Editores, S.A., 2017)
The Científicos Pack 2 gathers 6 of the most outstanding scientists in history. Paul Strathern presents an accurate and expert account of the life, ideas and discoveries of these six scientists and explains their influence on man's struggle to understand his existence in the world.